SISTEM INFORMASI MANAJEMEN ADMINISTRASI PKL DAN SKRIPSI (SIMADU) MENGGUNAKAN RAPID APPLICATION DEVELOPMENT (RAD): Studi Kasus: Fakultas Sains dan Teknologi UNIRA - Rijalul Baqi; Priska Choirina; Urnika Mudhifatul; Farid Wahyudi; Pangestuti Prima Darajat (Universitas Methodist Indonesia, 2022)
Universitas Islam Raden Rahmat as a university in Malang Regency at the Faculty of Science and Technology in carrying out Field Work Practice (PKL) and Thesis activities still collects documents physically and is required to meet with Lecturers for verification. So in this study the author aims to design and build a system that can assist the administrative process of street vendors and Thesis. The method used in data collection was done by literature study, interviews and observation. The system development method in this study uses Rapid Application Development (RAD) because it can develop software according to user desires and can accelerate development. The method in the system testing stage is using Black Box Testing. This information system was developed using the Laravel framework as the backend of the system. The result of this research is a Sistem Informasi Manajemen Administrasi PKL dan Skripsi (SIMADU) which can help manage administration in the Faculty of Science and Technology. Based on the test results, the system that was built is running well and getting a 100% success percentage. Therefore, the SIMADU that has been built can be implemented at the research location.